In vivo acquisition and risk of inter-species spread of blaKPC-3-plasmid from Klebsiella pneumoniae to Serratia marcescens in the lower respiratory tract. Issue 1 (6th January 2020) - Bielli, Alessandra; Piazza, Aurora; Cento, Valeria; Comandatore, Francesco; Lepera, Valentina; Gatti, Milo; Brioschi, Paolo; Vismara, Chiara; Bandi, Claudio; Perno, Carlo Federico
Abstract : In recent years, Serratia marcescens has emerged as an important agent of hospital-acquired infections, such as pneumonia, urinary tract infection, septicaemia and meningitis, particularly in vulnerable patients. Compared to Klebsiella pneumoniae and Escherichia coli, S. marcescens is less commonly associated with bla KPC genes, yet few cases of plasmid transmission at the gastrointestinal level from K. pneumoniae carbapenemase (KPC)-producing Enterobacterales to S. marcescens have been described. Here we report a case of in vivo acquisition, during a 3-month period of hospitalization in the intensive care unit, of a bla KPC-3 gene carried by a pKpQIL-IT plasmid, and its probable transmission at the bronchial level among different species of Enterobacterales, including K. pneumoniae and S. marcescens . By using whole genome sequence analyses we were able provide insight into the dynamics of carbapenem-resistance determinants acquisition in the lower respiratory tract, a novel anatomical region for such plasmid transmission events, that usually involve the gastrointestinal tract. The co-presence at the same time of both wild-type and resistant Enterobacterales could have been the critical factor leading to the spread of plasmids harbouring carbapenem-resistance genes, of particular importance during surveillance screenings. The possibility of such an event may have significant consequences in terms of antimicrobial treatment, with a potential limitation of therapeutic options, thereby further complicating the clinical management of high-risk critically ill patients.